A microhaplotypes panel for forensic genetics using massive parallel sequencing. (December 2017) - Turchi, Chiara; Pesaresi, Mauro; Tagliabracci, Adriano
Abstract: Microhaplotypes (microhaps) are defined as loci of two or more SNP within the span of a single sequencing run with three or more common allelic combination (haplotypes) of the SNPs. Microhaps appear to be useful in forensics for individual identification, ancestry inference, estimating relationships, and deconvoluting mixtures. The most important issue is identifying and characterizing a set of microhaps with the optimum characteristics for specific purposes and developing a suitable genotyping technology. The MPS technologies are now making microhaplotypes a new type of forensic marker: a single sequence read can cover the expanse of the microhaplotypes and these loci become phase-known. In the present study we selected a panel of 89 microhaps, from The ALlele FREquency Database and we evaluated these loci on 73 Italian samples. The results make the panel very informative for resolving DNA mixture, for identification and for recostruction of biological relationships. Microhaps will become a very promising new type of forensic marker when MPS is the technology being used for genotyping.